Antimicrobial stewardship – can we afford to do without it?. (February 2015) - Aryee, Anna; Price, Nicholas
<x xml:space="preserve">Abstract</x> Antimicrobial resistance (AMR) is a rapidly developing and alarming global threat which has been highlighted by national governments and public health bodies including the World Health Organization. The spectre of a 'post‐antibiotic era' is a real possibility unless curtailing the development and spread of these organisms is given high priority. Numerous studies have shown that AMR is associated with worse outcomes for patients and higher healthcare costs. While clinical data from low and middle income countries is lacking, there is increasing evidence that the problem in these areas is as great, or even greater, than in high income nations. Of the many drivers behind the development of AMR, the most significant is selection pressure caused by antibiotic use. Antimicrobial stewardship programmes are a set of interventions that aim to ensure the judicious use of antimicrobials by preventing their unnecessary use, and by providing targeted and limited therapy in situations where they are warranted. The ultimate goal of these programmes is to provide effective antimicrobial therapy whilst safeguarding their effectiveness for future generations. Whilst they do require an initial investment, they have been shown to be an effective way of controlling antimicrobial use, and have been associated with improved patient outcomes and reduced healthcare costs.